Structural Design and Electrical Characteristics Analysis of Mid-Load Whip Antenna - Menglei Xiu; Lihua Li; Shimin Feng (International Journal of Antennas and Propagation)
In order to facilitate the integration of the offshore surface antenna and reduce the manufacturing cost, the resonance shortening length and omnidirectional radiation performance of a centrally loaded whip antenna are analyzed. By calculating the impedance characteristics of each part of the midload whip antenna, the shortened length of the antenna in the resonance state is obtained; the superimposed field strength of the midload whip antenna to the far field is calculated and its radiation performance is analyzed; the simulation is carried out by using FEKO electromagnetic simulation software. Through the field test, the reflection coefficient and resonant frequency of the antenna before and after shortening are compared, and the directivity of the midload whip antenna and the traditional whip antenna is compared. The simulation and experimental results show that under the preset frequency of 75 MHz, the reflection coefficient of the shortened midload whip antenna decreases by 4.414 dB and 19.09 dB, respectively. The optimal operating frequency is about 68.6 MHz–79.4 MHz, and the bandwidth is 10.8 MHz. Compared with the traditional whip antenna, the midload whip antenna at the radiation null point receives a larger field strength.